Online readers between the camps: A Text World Theory analysis of ethical positioning in We Need to Talk About Kevin. (May 2017) - Nuttall, Louise
Recent investigations into ethical experiences of fictional narratives have discussed the 'positions' that readers adopt in relation to the author, narrator and characters . This article applies Text World Theory as a means of accounting for the ethical experience of Lionel Shriver's We Need to Talk About Kevin . Qualitative analysis of a sample of 150 online reader responses on the reading-based social network Goodreads reveals a range of ethical responses to the novel positioned between two interpretative 'camps' and the nature/nurture debate they reflect with regards to the character, Kevin. Drawing from this dataset, I explore how stylistic features of Shriver's epistolary novel could be seen to influence readers' ethical positioning in relation to the multiple perspectives presented at different levels of its narrative structure. As a result of the analysis, I propose that an account of ethical experience using Text World Theory may benefit from the concept of 'construal' in Langacker's Cognitive Grammar. By modeling readers' variable attention to multiple minds, including their own, a cognitive grammatical model of construal may support an understanding of ethical interpretation as an interpersonal experience within particular reading contexts.